Highly expressed SLCO1B3 inhibits the occurrence and development of breast cancer and can be used as a clinical indicator of prognosis - Tiantian Tang (Nature Portfolio, 2021)
Abstract The role of organic anion transporting polypeptide 1B3 (SLCO1B3) in breast cancer is still controversial. The clinical immunohistochemical results showed that a greater proportion of patients with negative lymph nodes, AJCC stage I, and histological grade 1 (P < 0.05) was positively correlated with stronger expression of SLCO1B3, and DFS and OS were also increased significantly in these patients (P = 0.041, P = 0.001). Further subgroup analysis showed that DFS and OS were significantly enhanced with the increased expression of SLCO1B3 in the ER positive subgroup. The cellular function assay showed that the ability of cell proliferation, migration and invasion was significantly enhanced after knockdown of SLCO1B3 expression in breast cancer cell lines. In contrast, the ability of cell proliferation, migration and invasion was significantly reduced after overexpress the SLCO1B3 in breast cancer cell lines (P < 0.05). Overexpression or knockdown of SLCO1B3 had no effect on the apoptotic ability of breast cancer cells. High level of SLCO1B3 expression can inhibit the proliferation, invasion and migration of breast cancer cells, leading to better prognosis of patients. The role of SLCO1B3 in breast cancer may be related to estrogen. SLCO1B3 will become a potential biomarker for breast cancer diagnosis and prognosis assessment.